ANALISIS FAKTOR RENDAHNYA MINAT BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS XI - Elva Yani; Dasa Ismaimuza; Siti Hanifah Naim (Universitas Tadulako, 2025)
This paper describes the analysis of factors that cause low student interest in learning mathematics. The research method used is a qualitative method to produce descriptive data in the form of written or spoken words from subjects and observable behavior. The purpose of the study was to find out in depth and try to find the underlying meaning of student interest in learning mathematics. Informants in the interview involved 5 people where 2 students became the main informants who had low mathematics scores, 2 parents, 1 homeroom teacher of class XI C3 SMA Negeri 03 Palu. To find out the factors of low student interest in learning mathematics, the researcher conducted direct observation and conducted interviews. After finding the results of the interview, the researcher obtained information that students who had low interest in learning mathematics were influenced by several factors. Among them are (1) students are not interested in learning mathematics, (2) lack of student motivation to learn, (3) insufficient student break time, and (4) parents never help students in learning.